Enhancing Students’ Problem-Solving Skills Through Group Counseling: A Case Study - Siregar, Fika Sundari; Tambusai, Khairuddin (Journal of Social Work and Science Education, 2025)
This study explores the effectiveness of group counselling services in improving students’ problem-solving skills within the environment of the Islamic Centre Foundation of North Sumatra. The background of this research is based on preliminary findings indicating that some students experience difficulties in addressing and resolving problems they encounter, both in school and in daily life. This study employs a qualitative approach using a case study method, allowing the researcher to deeply observe the counselling intervention process in its natural context. The research subjects consisted of several students selected purposively based on initial assessments that revealed low levels of problem-solving skills. Data collection was conducted through participatory observation, in-depth interviews, and document analysis, carried out continuously over six group counselling sessions. Each session was designed to guide students in systematically identifying problems, exploring alternative solutions, considering the consequences of each option, and making rational and responsible decisions. The findings of the study show a significant improvement in key aspects of students’ problem-solving skills, as reflected in changes in their attitudes and behaviours when facing problematic situations at school and at home. These results reinforce the view that group counselling can serve as an effective intervention strategy to help students develop critical thinking abilities and adaptive social skills. Based on these findings, it is recommended that schools and educational institutions integrate group counselling services into their student development programs, particularly in fostering life skills. Furthermore, school counsellors are encouraged to design structured, student-centred counselling sessions to enhance the effectiveness of the services provided.